United States Intervention on the Cross-Strait Escalation between China and Taiwan - Irene, Irene (PT FORMOSA CENDEKIA GLOBAL, 2024)
The changes occurring in the structure of the international system are undoubtedly influenced by various factors in the dynamics of interactions among nations. The success of a country in bolstering its material strength inherently poses a threat to other nations with strategic interests in the region. From a realist perspective, there is an observation of attempts by a hegemonic state to pursue its national interests by seeking to influence the capabilities of other nations. In the Cross-Strait interactions between Taiwan and China, the role of the United States is undoubtedly integral and determines the escalation of tension across the strait. Efforts to establish a sovereign and democratic government, coupled with Taiwan's strategic location in the projection of U.S. national interests, introduce a new layer of complexity to the structure of the international system. The increasingly close cooperation between the United States and Taiwan, particularly in military and economic aspects, will impede China's efforts to achieve reunification. The commitment of the United States to interpreting the One-China policy tends to change with each administration, inevitably escalating tensions in the region. Consequently, Taiwan remains a decisive factor in U.S. control in the region, especially in preserving democracy and attaining other strategic objectives.